2019
DOI: 10.3389/fimmu.2019.02482
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Anaphylaxis: Data From the European Anaphylaxis Registry

Abstract: Refractory anaphylaxis (unresponsive to treatment with at least two doses of minimum 300 μg adrenaline) is a rare and often fatal hypersensitivity reaction. Comprehensive data on its definition, prevalence, and risk factors are missing. Using the data from the European Anaphylaxis Registry (11,596 cases in total) we identified refractory anaphylaxis cases (n = 42) and analyzed these in comparison to a control group of severe anaphylaxis cases (n = 4,820). The data show that drugs more frequently elicited refra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 38 publications
0
50
0
3
Order By: Relevance
“…Using the data from the European Anaphylaxis Registry (11,596 cases in total), 42 cases of refractory anaphylaxis of different origin were identified and compared to a control group of severe anaphylaxis cases (n = 4820). Cases elicited by insects were very few (n = 8) and often due to bee stings (76). Specific risk factors were not identified in Hymenoptera venom-allergic patients.…”
Section: Patients Refractory To Medicationmentioning
confidence: 93%
“…Using the data from the European Anaphylaxis Registry (11,596 cases in total), 42 cases of refractory anaphylaxis of different origin were identified and compared to a control group of severe anaphylaxis cases (n = 4820). Cases elicited by insects were very few (n = 8) and often due to bee stings (76). Specific risk factors were not identified in Hymenoptera venom-allergic patients.…”
Section: Patients Refractory To Medicationmentioning
confidence: 93%
“…The term 'refractory anaphylaxis' is not clearly defined. We used the definition from a previous study [6], which described refractory anaphylaxis as a condition that required more than two doses of 0.3 mg intramuscular epinephrine for complete symptom resolution. According to the definition, the enrolled patients were divided into two groups: refractory and non-refractory anaphylaxis.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…A previous study by Korenblat et al reported that 17 out of 105 patients (16.2%) required three or more intramuscular epinephrine injections [28]. A more recent analysis of the European Anaphylaxis Registry by Francuzik et al reported that only less than 1% of severe anaphylaxis cases were refractory to epinephrine treatment [6]. The variation in disease prevalence may be because of epidemiologic factors.…”
Section: Incidence Of Refractory Anaphylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Well-maintained registries provide a temporal profile of how chronic conditions are being managed, e.g., the Finnish National Anaphylaxis Registry and the European Anaphylaxis Registry (refractory anaphylaxis data) [5, 6]. However, such data is only effective in leading to policy change if it remains highly accurate from the primary point of entry to the methodologies used to interpret and analyse it.…”
mentioning
confidence: 99%